Investigation of Hydrocarbon Stapled Alpha-Helical Peptides as a Novel Method to Interrupt Protein-Target Interactions in Bacteria - Pau, Daniel (Université d'Ottawa / University of Ottawa, 2016)
With the increasing threat of multidrug resistant bacteria, there is a growing need to invent new drug classes that combat untreatable infections. Small molecule antibiotics have been successful in the past, but humanity is now losing the arms race against previously treatable pathogens. However, the number of clinically approved drugs targeting traditionally undruggable targets in bacteria remains low. New targets of complex protein-target interactions must be targeted for future pharmacological development. In an effort to create clinically viable biologics, the Verdine lab has developed a class of therapeutics called hydrocarbon stapled α-helical peptides; these peptides are known to affect protein-protein interactions by retaining secondary structure in vivo. Although this class of molecules has been extensively researched in cancer and viral therapies, there has been little work in bacteria due to the proposed endocytic method of entry. Moreover, DNA-binding stapled peptides have not been extensively investigated due the complexities in designing a peptide with gene selectivity. In an attempt to study peptides in bacteria, two stapled peptides based on the RpoN domain of σ54 and the FtsZ C-terminus have been synthesized. σ 54 is a DNA-binding co-factor of RNA polymerase (RNAP) and has been shown to regulate virulence and nitrogen and carbon metabolism. FtsZ is the structural unit of the contractile Z-ring that induces cell division. By designing stapled α-helical peptides to target these untraditional PPIs, we anticipate that these molecules may be used for future antimicrobial pharmacological development that treat multidrug resistant bacteria.
Keywords: Stapled peptides; Transcriptional Inhibitor; Sigma54; FtsZ; bacteria; antivirulence; antibiotics